Changes in self‐concept and risk of psychotic experiences in adolescence: a longitudinal population‐based cohort study. (16th February 2019) - Healy, Colm; Coughlan, Helen; Williams, James; Clarke, Mary; Kelleher, Ian; Cannon, Mary
Abstract : Background: Psychotic experiences (PEs) are commonly reported in adolescence and are associated with a range of negative outcomes. Few targets for intervention for PEs have been identified. One potential target is self‐concept: an individual's beliefs about his/her personal attributes. Improvements in self‐concept have been shown to reduce psychotic symptoms in patients with schizophrenia but no study has investigated the relationship between changes in self‐concept and risk of PEs in the general population. We aimed to investigate: (a) the relationship between child and adolescent self‐concept and adolescent PEs; and (b) whether changes in self‐concept between childhood and adolescence were associated with risk of adolescent PEs. Method: Using data from age 9 and age 13 ( n  = 7, 423) of the child cohort (Cohort'98) from the Growing Up in Ireland study we investigated the relationship between self‐concept at age 9 and age 13 and PEs at age 13. PEs were measured using the Adolescent Psychotic Symptoms Screener and self‐concept was measured using the Piers Harris‐II. Using a stratified analysis, we investigated the relationship between change in self‐concept between age 9 and age 13 and the risk of PEs at age 13. Additionally we investigated changes across the six self‐concept subscales. Results: Psychotic experiences were reported by 13% of participants at age 13. 'Very low' self‐concept at age 9 was associated with an increased risk of PEs at age 13 (Adjusted‐OR: 2.74, CI: 1.80–4.19), and 'High' self‐concept at age 9 was associated with a decreased risk of PEs at age 13 (Adjusted‐OR: 0.77, CI: 0.60–0.97). The stratified analysis indicated that improvements in self‐concept reduced the odds of adolescent PEs and decline in self‐concept increased the odds of adolescent PEs. This effect was noted across the majority of the self‐concept subscales. Conclusions: There is a strong relationship between self‐concept and PEs. The antecedents of low self‐concept may be a useful target for preventative psychiatry. Broad‐spectrum interventions targeting self‐concept in childhood may help to reduce the incidence of PEs in adolescence.